Hospitalist and Internal Medicine Leaders' Perspectives of Early Discharge Challenges at Academic Medical Centers. Issue 6 (6th December 2017) - Patel, Hemali; Fang, Margaret C.; Mourad, Michelle; Green, Adrienne; Wachter, Robert M.; Murphy, Ryan D.; Harrison, James D.
Abstract : Improving early discharges may improve patient flow and increase hospital capacity. We conducted a national survey of academic medical centers addressing the prevalence, importance, and effectiveness of early‐discharge initiatives. We assembled a list of hospitalist and general internal medicine leaders at 115 US‐based academic medical centers. We emailed each institutional representative a 30‐item online survey regarding early‐discharge initiatives. The survey included questions on discharge prioritization, the prevalence and effectiveness of early‐discharge initiatives, and barriers to implementation. We received 61 responses from 115 institutions (53% response rate). Forty‐seven (77%) "strongly agreed" or "agreed" that early discharge was a priority. "Discharge by noon" was the most cited goal (n = 23; 38%) followed by "no set time but overall goal for improvement" (n = 13; 21%). The majority of respondents reported early discharge as more important than obtaining translators for non‐English‐speaking patients and equally important as reducing 30‐day readmissions and improving patient satisfaction. The most commonly reported factors delaying discharge were availability of postacute care beds (n = 48; 79%) and patient‐related transport complications (n = 44; 72%). The most effective early discharge initiatives reported involved changes to the rounding process, such as preemptive identification and early preparation of discharge paperwork (n = 34; 56%) and communication with patients about anticipated discharge (n = 29; 48%). There is a strong interest in increasing early discharges in an effort to improve hospital throughput and patient flow.